(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Marketing cost forms a major costarea in the Fertilizer Industry. By controlling this cost element, the industrycan achieve a significant measure of economy in all its operations and therebysave the exchequer by reducing the quantum of subsidy, in addition to improvingthe profitability of fertilizer units.